Online lectures evaluation system - Mariani Mohd Rajab
This project focused on the development and testing of user friendly online software that is able to gather data (inputs from students) used for Lecturers' teaching evaluation. The system will developed by using MySQL as database engine, Apache as Server and PHP as web scripting language.